Notes on some Indo-Pacific Caridean shrimps (Crustacea: Decapoda: Caridea: Palaemonidae and Gnathophyllidae) particularly from India - Prakash, Sanjeevi; Kumar, Thipramalai Thangappan Ajith; Subramoniam, Thanumalaya (Zootaxa, 2015)
Although among the less conspicuous members of the tropical shallow reef fauna, the caridean shrimps are not less abundant. Much scope for further study on the marine carideans of Indian waters still exists and many species must certainly remain to be discovered. Although, the recent checklist on prawn fauna of Indian waters reports 285 species of caridean shrimps (including fresh water forms) (Radhakrishnan et al, 2012). With this, the present study also contributes another report on the documentation of six species of caridean shrimps from the Gulf of Mannar and Lakshadweep waters of Indian peninsula. Out of six species Ancylomenes magnificus (Bruce), Periclimenes soror Nobili, Stegopontonia commensalis Nobili, Gnathophyllum americanum Guerin Meneville and Gnathophylloides mineri Schmitt are new to the Indian fauna. In the present paper, detailed notes on species description, color pattern, distribution, habitat and hosts were discussed.